Voluntary medical male circumcision among adolescents: a missed opportunity for HIV behavioral interventions. (1st July 2017) - Kaufman, Michelle R.; Dam, Kim H.; Van Lith, Lynn M.; Hatzold, Karin; Mavhu, Webster; Kahabuka, Catherine; Mahlasela, Lusanda; Marcell, Arik V.; Patel, Eshan U.; Figueroa, Maria Elena; Njeuhmeli, Emmanuel; Seifert-Ahanda, Kim; et al.
Abstract : Objective: Voluntary medical male circumcision (VMMC) is one of the first opportunities for adolescent males in African countries to interact with the healthcare system. This study explored the approaches used during adolescent VMMC counseling and whether these strategies maximize broader HIV prevention opportunities. Methods: Qualitative interviews were conducted with 92 VMMC clients ages 10–19 years in South Africa ( n = 36), Tanzania ( n = 36), and Zimbabwe ( n = 20) and 33 VMMC providers across the three countries. Discussions explored HIV prevention counseling, testing, and disclosure of results. Audio recordings were transcribed, translated into English, and coded thematically by two individuals. Results: Male adolescents in all three countries reported that limited information was provided about HIV prevention and care, and adolescents were rarely provided condoms. Although VMMC protocols require opt-out HIV testing, adolescents recounted having blood taken without knowing the purpose, not receiving results, nor completely understanding the link between VMMC and HIV. Most males interviewed assumed they had tested negative because they were subsequently circumcised without knowing test results. Providers reported spending little time talking about HIV prevention, including condom use. They admitted that younger adolescent clients often receive little information if assumed they are not sexually active or too young to understand and instead discussed nonsexually transmitted routes of HIV. Conclusion: In the sites of the three countries studied, HIV prevention and care messages were inconsistent and sometimes totally absent from VMMC counseling sessions. VMMC appears to be a missed opportunity to engage in further HIV prevention and care with adolescents.